Arthropod fauna of winter wheat of southwest Buenos Aires province, Argentina - Pompozzi, Gabriel Alejandro (2014)
Agroecosystems are populated by a great diversity and number of invertebrates that are often disturbed by agricultural practices and grazing. The arthropods are good indicators of the heterogeneity of the habitat, the biodiversity of the ecosystem and the stress conditions of the environment, therefore its use for environmental management can reduce pest invasion. The goals of this study are to describe the composition of the arthropod fauna and to analyze how this fauna are distributed throughout the phenological development in a crop of winter wheat at southwestern Buenos Aires Province. Two sampling methods were conducted: at ground level by using pit-fall traps and herbaceous level using a garden-vacuum. A total of 29608 arthropods were collected belonging to 19 orders. The most abundant order was Diptera, followed by Hemiptera, Collembola, Hymenoptera, Acarii, Coleoptera and Araneae. The abundance of the arthropod community associated with the crop increased in the last phenological stages of it. This study comprises one of the first approaches involving the study of the arthropod fauna associated with a winter wheat crop at southwestern Buenos Aires Province, and also is one of the few contributions about this topic in Argentina.